The Golden Horde Relics in the Charters of Medieval Moldavia: General Sketch of the Case “Kishinev” - N.D. Russev (Золотоордынское обозрение)
Researchers are well aware that a part of the Moldovan lands belonged to the Golden Horde. But this period is still not sufficiently studied due to the lack of information, especially in written sources. The author of this article has attempted to expand the source base of the investigated issue by compiling information about the “Tatars” from the medieval charters of Moldova. The author demonstrates that the systematic study of the contents of hundreds of surviving diplomatic monuments enables a more complete reconstruction of local realities during the Golden Horde era. In particular, we can localize individual uluses of the Jochid leaders and find out the direction of the main trends of migration and social transformation of the “Tatars” in the socio-political conditions of the Moldovan statehood. An analysis of the place names such as “Kishinev”, mentioned in charters, sheds light on the nature of the adaptation of the surviving population at the right-bank of the Dniester region under the authority of the Moldavian rulers at the end of the 14th–15th centuries